Relatıonshıp Between School Clımate And Prıncıpals’ Job Performance In Secondary Schools - Perpetua N. Okorji; Innocent C. Igbokwe; Carol O. Ezeugbor (European Scientific Journal, ESJ, 2016)
This study investigated the relationship between school climate and principals’ job performance in secondary schools in Enugu State, Nigeria. It adopted a correlational study design. Five research questions and five hypotheses guided the study. The population of the study embraced all the principals from 283 secondary schools in the six education zones of Enugu State. Out of the population, a sample of 177 principals was selected through simple random sampling technique. The instruments used to collect data were Organizational Climate Index and Principal Self-Assessment Questionnaire, adapted and developed by the researcher, respectively. The two sets of questionnaires were duly validated by experts in Measurement and Evaluation, and Educational Management and Policy. Cronbach Alpha method was used to determine the reliability coefficient of the instruments which yielded 0.83 for the Organizational Climate Index and 0.94 for the Principal Self-Assessment Questionnaire. . Pearson Product Moment correlation coefficient was used for data analysis. The findings showed among others that: there was a moderate positive relationship existing between the two variables- school climate and principal’s job performance. Based on the findings of the study, it was recommended that principals should embrace the collaborative and collegial style of administration where teachers are included and free to share ideas and concepts for managerial and school effectiveness. It was also recommended that principals should create an atmosphere that is supportive, comfortable, friendly, productive, and relaxed, to motivate students’ greater participation in learning and achieving educational goals.